IMPACT OF GOVERNMENT POLICY AND RATIONALITY OF THE SMOKER TO THE CIGARETTE CONSUMPTION IN INDONESIA - Noor Syaifuddin (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
Even though there is high need of the excise revenue from a cigarette, but the government of Indonesia needs to take into account the long run effect of cigarette to the people. There are poverty, health and education issues relating to the cigarette consumption. Therefore, the government intervention can help people to curb the cigarette consumption. This study attempts to find the impact of the government policy through the excise tariff policy, and the rationality of the smoker to the cigarette consumption in Indonesia. This study recommends the government intervention in order to control the cigarette consumptions in Indonesia by pushing the cigarette price and making cigarette less affordable for less rationale smoker (the young and poor people). Secondly, the government can take an action in delimiting the access of cigarette advertising and educate people about the danger of cigarette to the people.